2011
DOI: 10.1210/jc.2011-0047
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Adipokines and Ghrelin on Bone Mineral Density and Fracture Risk: A Systematic Review and Meta-Analysis

Abstract: Adiponectin is the most relevant adipokine negatively associated with BMD, independent of gender and menopausal status. Inconsistent associations between adipokines and BMD are probably confounded by body composition, in particular fat mass parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
164
4
17

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(193 citation statements)
references
References 95 publications
8
164
4
17
Order By: Relevance
“…Evidence from a systemic review and meta-analysis showed that adiponectin is the most relevant adipokine negatively associated to BMD, independent of gender, menopausal status, and fat mass parameters [48]. Therefore, human studies suggest adiponectin as a negative factor for BMD.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from a systemic review and meta-analysis showed that adiponectin is the most relevant adipokine negatively associated to BMD, independent of gender, menopausal status, and fat mass parameters [48]. Therefore, human studies suggest adiponectin as a negative factor for BMD.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, general obesity and body weight are the strongest protectors against bone loss by exercising greater load on the lower limbs and trunk [32]. Other mechanisms related to obesity may also explain its protective effect such as higher 17β-estradiol [33][34][35] and insulin [36] levels, and some adipokines especially lower adiponectin and higher leptin [37][38][39]. Also, it seems that visceral obesity is influencing mainly trabecular bone [40].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have described various cytokines that are implicated in bone and adipose tissue crosstalk [17,18].…”
Section: Discussionmentioning
confidence: 99%